Impact of Efficient Resource Management Practices on Sustainable Performance: Moderating Role of Innovative Culture-Evidence From Oil and Gas Firms - Wang, Yihan; Zhang, Shaojie; Xu, Shilin (Frontiers in Psychology, 2022)
Academics and practitioners have paid close attention to waste, energy, and resource management due to growing awareness of its effects on sustainable performance. This study aims to explore the status and challenges of efficient resource management in China, an under-researched area. Moreover, it proposes a theoretical framework to fill the academic and practical gap how efficient resource management practices can build sustainable performance. This study justifies the need to explore the need of efficient resource management practices in emerging economies like China. Empirical data derived using a cross-sectional survey of 265 employees from oil and gas firms in China were used to test the theoretical framework developed from mainstream literature. Empirical findings of this study highlight the role of efficient resource management practices such as CSR, process and equipment, human resource practices, product design, and manufacturing planning which have a positive and significant impact on sustainable performance. In addition, innovative culture plays a moderating role in enhancing firms' sustainable performance. The findings suggest that there is further scope to utilize the efficient resource management practices for encouraging innovative culture to build sustainable performance. This study creates a basis for future research of building sustainable organizational performance by integrating efficient resource management practices. This study also highlights gaps in the system and provides insights into policymakers and manufacturing sector employees on holistically building a sustainable organization.